Long term blood metal ion levels and clinical outcome after Birmingham Hip Arthroplasty - Lindström, Miro (My University, 2021)
Our aim was to assess long-term metal ion level changes and clinical outcome in patients with a Birmingham Hip arthroplasty. Our findings were that patients with a Birmingham hip device do not seem to benefit from frequent repeated metal ion measurements. The amount of patients with metal related adverse events was relatively high, but many of them did not require surgery.